What is the best pharmacologic management of insomnia in patients with COPD?. Issue 9 (September 2016) - Jakowski, Nathan; Kraus, Connie
Abstract : Evidence‐Based Answer : Triazolam and zolpidem increase total sleep time (TST) by 23 to 52 minutes in patients with chronic obstructive pulmonary disorder (COPD) who have insomnia while preserving oxygen saturation (SaO2 ) (SOR: C, single small crossover trial). Ramelteon increases TST by 27 to 41 minutes with no effect on SaO2 in patients with COPD who do not have insomnia (SOR: B, consistent small crossover trials). Benzodiazepines should be avoided in patients with COPD because of potential deleterious effects on ventilation (SOR: C, based on expert opinion).